The social life of books: Reading together in the eighteenth-century home - Williams, A (Yale University Press, 2017)
Two centuries before the advent of radio, television, and motion pictures, books were a cherished form of popular entertainment and an integral component of domestic social life. In this fascinating and vivid history, Abigail Williams explores the ways in which shared reading shaped the lives and literary culture of the time, offering new perspectives on how books have been used by their readers, and the part they have played in middle-class homes and families. Drawing on marginalia, letters and diaries, library catalogues, elocution manuals, subscription lists, and more, Williams offers fresh and fascinating insights into reading, performance, and the history of middle-class home life.